Epilepsy, E/I balance and GABAA receptor plasticity - Fritschy, Jean-Marc (Frontiers in Molecular Neuroscience, 2008)
GABAA receptors mediate most of the fast inhibitory transmission in the CNS. They form heteromeric complexes assembled from a large family of subunit genes. The existence of multiple GABAA receptor subtypes differing in subunit composition, localization and functional properties underlies their role for fi ne-tuning of neuronal circuits and genesis of network oscillations. The differential regulation of GABAA receptor subtypes represents a major facet of homeostatic synaptic plasticity and contributes to the excitation/inhibition (E/I) balance under physiological conditions and upon pathological challenges. The purpose of this review is to discuss recent fi ndings highlighting the signifi cance of GABAA receptor heterogeneity for the concept of E/I balance and its relevance for epilepsy. Specifi cally, we address the following issues: (1) role for tonic inhibition, mediated by extrasynaptic GABAA receptors, for controlling neuronal excitability; (2) signifi cance of chloride ion transport for maintenance of the E/I balance in adult brain; and (3) molecular mechanisms underlying GABAA receptor regulation (traffi cking, posttranslational modifi cation, gene transcription) that are important for homoeostatic plasticity. Finally, the relevance of these fi ndings is discussed in light of the involvement of GABAA receptors in epileptic disorders, based on recent experimental studies of temporal lobe epilepsy (TLE) and absence seizures and on the identifi cation of mutations in GABAA receptor subunit genes underlying familial forms of epilepsy.